2019
DOI: 10.22460/project.v2i1.p94-101
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Meaning Analysis of Adele’s Song Lyric in 21 Album

Abstract: Songs are one of media in language to communicate or deliver a message which created by a songs’ writer through a singer to listeners. Songs is very effective as a media in analyzing systemic functional linguistic, because in song contained two text at once, those are when a singers sing, the song is the spoken text, and the song lyric is the written text. The objective of this study is to describe the aspects of Interpersonal Meaning in the lyric of Adele’s Album 21. The design of the research was descriptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In addition, the study is also expected could give additional information for the furtherer research on the same topic. Many have conducted figurative language analysis in song lyrics, such as -Endless Love‖ (Ibrahim et al, 2019), -Don't You Remember‖ by Adele (Sari, Dartini, & Mulyani, 2019), -One OK Rock‖ (Rahim, 2019). Similarly, the findings showed that all songs they investigated have figurative languages.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the study is also expected could give additional information for the furtherer research on the same topic. Many have conducted figurative language analysis in song lyrics, such as -Endless Love‖ (Ibrahim et al, 2019), -Don't You Remember‖ by Adele (Sari, Dartini, & Mulyani, 2019), -One OK Rock‖ (Rahim, 2019). Similarly, the findings showed that all songs they investigated have figurative languages.…”
Section: Introductionmentioning
confidence: 99%
“…Song is a part of literature (Siallagan, et. al., 2017) cited in (Sari, et al, 2019). The song lyrics vary in terms of textual meaning.…”
Section: Song Lyricsmentioning
confidence: 99%